Bats like vintage: managing exotic eucalypt plantations for bat conservation in a Mediterranean landscape. (23rd June 2015) - Cruz, J.; Sarmento, P.; Rydevik, G.; Rebelo, H.; White, P. C. L.
Abstract: The transformation of native habitats into forest plantations for industrial purposes frequently has negative consequences for biodiversity. We evaluated the impact of eucalypt plantations on native bats in a Mediterranean area, taking Portugal as a case study. We compared the overall bat activity, species richness and Kuhl's bat P ipistrellus kuhlii (the most abundant bat species in the area) activity between eucalypt plantations and native montado habitat, and examined the influence of stand, landscape and survey variables within plantations on the response variables. A set of 11 plantation stands, three landscape and two survey variables were employed as predictor variables using a zero‐inflated Poisson generalized linear mixed model. Hawking and generalist bats of the genus P ipistrellus were the most frequently detected species. Bat activity, species richness and P . kuhlii activity were higher in native montado than in any of the eucalypt stands. Mature eucalypt plantations showed the highest bat activity, while clear‐cut areas showed the lowest. Generally, within eucalypt stands, complex high‐level vegetation structure, from the ground level up to 3 m high, and proximity to water points were associated with higher levels of bat and P . kuhlii activity and species richness. The results suggest that in order to promote bat diversity and activity in exotic eucalypt plantations in the Mediterranean region, it is important to provide a high density of water points, maintain plots of mature plantations and promote understorey clutter.